Evaluation of the Performance of Urban Transportation on the Cilegon-Bojonegara Route in Cilegon City Using the Servqual Method - Pradana, Muhammad Fakhruriza; Lestari, Neng Suci; Bethary, Rindu Twidi; Budiman, Arif; Intari, Dwi Esti; Suzanti, Wiwien (JURUSAN TEKNIK SIPIL, 2026)
This study evaluates the quality of urban transportation services on the Cilegon – Bojonegara route using the servqual method, which assesses the gap between passenger perception and expectations on five service dimensions. Data was obtained through questionnaires and field observations. The results of the study showed that all dimensions had a negative gap, with an average perception of 3.184 and an expectation of 4.005 The largest gap was in the guarantee dimension with a gap value of -0.960, followed by physical evidence, empathy and reliability. Meanwhile, responsiveness has the smallest gap with a value of -0.663. This indicates that the city's transportation services have not met passenger expectations, especially related to passenger comfort and safety, drivers drive recklessly. Recommendations for improvement include improving the quality of city transportation safety by optimizing driving speed to stay safe and not reckless, Improving the timeliness and clarity of the route by optimizing travel time so that it is not delayed, providing clearer routes and routes to passengers. The improvements are expected to improve service quality and customer satisfaction.